1999
DOI: 10.1111/j.1528-1157.1999.tb00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Interactions as Targets for Intervention to Improve Social Adjustment After Epilepsy Surgery

Abstract: Summary: Purpose: To identify family interactions associated with psychosocial outcome of epilepsy surgery, to design interventions to improve patient outcome.Methods: A cross-sectional, case series study of relations among observed family behavior and psychosocial outcome of 43 patients after temporal lobectomy. Videotaped family behavior during family discussion tasks was rated for predominant family affect, affective range, and support of patient autonomy. Multiple regression analyses tested the relation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…44 1989 151 patients and 249 family members A study of psychiatric problems in families of epilepsy showing increased problems in mothers and spouses. Langfitt et al 55 1999 43…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 1989 151 patients and 249 family members A study of psychiatric problems in families of epilepsy showing increased problems in mothers and spouses. Langfitt et al 55 1999 43…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have suggested that the family environment may be important in the course of the disorder and influence both the severity and impact of the condition. Furthermore, this may negatively impinge on the family unit and its functioning 7,17,18,20,[55][56][57][58][59] .…”
Section: The Family Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1994 there have been several developments in the understanding of patients needs that highlight the importance of considering psychological wellbeing, patient expectations and family dynamics when assessing the likely psycho-social and quality of life benefits of epilepsy surgery [5][6][7] . A growing number of § On behalf of the Psychologists in Epilepsy Group.…”
Section: Introductionmentioning
confidence: 99%
“…(Mihari, Inoue, Watanabe, et al, 1994). Finally, Langfitt, Wood, Brand, et al (1999) examined family factors that may contribute to better postoperative adjustment in patients. Their cross‐sectional case series study of observed family interactions demonstrated that patients displayed better postoperative social adjustment in families in which the patient's autonomy was respected and family members demonstrated emotional support.…”
mentioning
confidence: 99%